Human rights protection in the context of combating terrorism: problems of finding the optimal balance - Волощук, Оксана Троянівна; Волощук, О. Т.; Волощук, Оксана Трояновна; Voloshchuk, Oksana T.; Колесник, Вікторія Юріївна; Колесник, В. Ю.; Колесник, Виктория Юрьевна; Kolesnyk, Viktoriia Yu.; Шевчук, Андрій Васильович; Шевчук, А. В.; Шевчук, Андрей Васильевич; Shevchuk, Andrii V.; et al. (Editorial Primmate S. A. S., 2021)
The article examines the essence and nature of terrorism in the light of the problem of observance and protection of human rights, as well as analyzes the problems that arise in the implementation of anti-terrorist activities. Emphasis is placed on the fact that it is difficult to find a balance in the observance of human rights in the implementation of various anti-terrorist measures by law enforcement agencies and the investigation of crimes related to terrorist activities. It is concluded that the fight against terrorism and the protection of human rights are goals that cannot conflict with each other in a democratic society. They complement and mutually reinforce each other, so when taking measures to stop terrorist activities, states are obliged to adhere to key principles and norms of international law, as well as specific commitments made in connection with participation in international human rights agreements.

У статті досліджуються питання сутності та природи тероризму у світлі проблеми дотримання та захисту прав людини, а також аналізуються проблеми, які виникають при здійсненні антитерористичної діяльності. Акцентується увага на тому, що складно знайти баланс у дотриманні прав людини при здійсненні різного роду антитерористичних заходів правоохоронними органами та розслідуванні злочинів, пов’язаних із здійсненням терористичної діяльності. Зроблено висновок про те, що боротьба з тероризмом та захист прав людини - цілі, які не можуть конфліктувати між собою у демократичному суспільстві. Вони доповнюють і взаємно підсилюють один одного, тому при вжитті заходів, спрямованих на припинення терористичної діяльності держави зобов'язані дотримуватися ключових принципів і норм міжнародного права, а також конкретних зобов'язань, прийнятих у зв'язку з участю в міжнародних угодах з прав людини.
Vоlоshchuk О. Human rights protection in the context of combating terrorism: problems of finding the optimal balance / O. Voloshchuk, V. Kolesnyk, A. Shevchuk, O. Yushchyk, P. Krainii // Amazonia Investiga. – Vol. 10. – Iss. 45. – Editorial Primmate S. A. S., 2021. – P. 73-81.
Keywords: terrorism; terrorist activity; human rights; restriction of human rights; counteraction to terrorism; тероризм; терористична діяльність; права людини; обмеження прав людини; протидія тероризму; Research Subject Categories::LAW/JURISPRUDENCE